(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2011)
Starting from the problem of correspondence between words and things, immagine and objects, I analyze Wittgenstein’s notion of übersichtlichen Darstellung in relation with comprehension. This relation is possible thanks to our capacity to see connections. The thesis I support claims that, in order to clarify this point, it is important to take into consideration Spengler’s Philosophy, that is undoubtedly a Wittgenstein’s source. I also refer to Goethe, who is called by Wittgenstein against Spengler on the topic of the distinction between the experimenter subject and object of the experimentation.